10.61533 EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL TERHADAP PERSEDIAAN BARANG DAGANG DI CV MM ACING JAYA TUATUNU PANGKALPINANG - Sherly Tabita, Jessintha; Oktalina, Gayatria; Novika (Jurnal Ilmiah Niaga Bisnis Elektronik, 2024)
This thesis, written and compiled by Jessintha Sherly Tabita with Student Identification Number 540200024, is titled “Effectiveness of the Internal Control System on Merchandise Inventory at CV MM Acing Jaya Pangkalpinang." The study aims to understand the internal control system over merchandise inventory at MM Acing Jaya Pangkalpinang. Data collection techniques included observation, interviews, and documentation. The data analysis technique used was descriptive-qualitative. The results show that the internal control system over merchandise inventory at MM Acing Jaya Pangkalpinang is largely in accordance with the theoretical standards of COSO Most of the components of the control environment are in place, but they have not been effectively implemented due to the absence of documents regulating the control environment. The control activities are also in place but not effective, as there are still frauds outside the store's supervision committed by drivers. Information and communication are in place but not yet effective, as some documents are still difficult to locate when needed.